The prevention, intervention and post-vention of suicide in the Republican National Guard - Ferreira, Luís (2024)
In Portugal, the suicide in the Security Forces has reached values higher than those of the general population, which reflected a need to seek solutions. This study aimed to understand the problem of suicide in the Republican National Guard through the identification of causes and consequences, the understanding of the intervention carried out in this field, and the identification of the post-vention as a prevention axis. Using the qualitative approach, through interpretative phenomenological analysis, nine semi-structured interviews were conducted with military personnel of the Republican National Guard and external entities. As conclusions, there was a greater focus on strengthening the institutional response in terms of suicide prevention, especially in post-vention. However, there is a need to optimize resources for training and post-intervention.